Photometric Determination of Fe(III) After Adsorption of its 1-Hydroxy-1-(p-Chlorophenyl)-3-Phenyl-2-Thiourea Complex on Microcrystalline Naphthalene - Mehra, Rita; Mathur, S.P. (Asian Journal of Chemistry, 2010)
The photometric determination of iron(III) with 1-hydroxy- 1-(p-chlorophenyl)-3-phenyl-2-thiourea is described. A stable water insoluble complex formed with iron and 1-hydroxy-1-(p-chlorophenyl)- 3-phenyl-2-thiourea is easily adsorbed from aqueous solution on micro- crystalline naphthalene. The solid mass is separated from aqueous solution, dried and dissolved in dimethylformamide. The absorbance of the solution is measured at 410 nm. Beer's law is obeyed in the concentration range of 10–170 μg of iron(III) in 10 mL of DMF. The molar absorptivity was found to be 2.11 X 104 L mol–1 cm–1 at 410 nm and the sensitivity being 1.73 x 10–2 μg cm–2 of Fe(III) for the absorbance of 0.001.